Hidroksiklorokin retinopatisi - (:unkn) unknown (My University, 2004)
Hidroksiklorokin retinopatili bir olgu ile retinopatinin tespitinde hasta takibinin önemini vurgulamak.55 yaşında sistemik lupus eritematosus tanısı ile üç yıldır hidroksikolorokin kullanmakta olan bayan hasta polikliniğimize başvurdu. Hastanın muayenesi yapılarak takip için kontrollere çağrıldı. Hasta verilen randevulara gelmedi ve ondört ay sonra görmede azalma şikayeti ile tekrar kliniğimize başvurduğunda görmeleri sağda 3/10 ve solda 6/10’a gerilemişti. Fundus muayenesindeki bilateral hedef göz (bull’s eye) görünümü ile hidroksiklorokin retinopatisi tanısı konuldu. Bu esnada hastanın kullandığı toplam doz 438 g’dı. Hastanın ilacı kesildikten sonra retinopati ilerledi ve görmeleri bilateral 1/10’a kadar geriledi.Hidrosiklorokin retinopatisi ileri derecede ve geri dönüşümsüz görme kaybı oluşturabilir. Bu nedenle hastaların yakın takibi gereklidir.

In order to validate the importance of regular follow-ups in hydroxychloroquine retinopathy, we described a case with hydroxychloroquine toxicity.A-55 year old woman with systemic lupus erythematosis was referred to our clinic who was using hydroxychloroquine for three years. She was told to have regular ophthalmologic examinations that she did not come. Fourteen months later, she came with the complaint of decreasing visual acuity which were 3/10 and 6/10 for the right and left eye respectively. Her fundus examination revealed bilateral bull’s eye at macula leading to diagnosis of hydoxychloroquine retinal toxicity. Total dosage at this time was 438 g. Her visual detoriation continued to bilateral 1/10 level after discontinuation of the drug.Hydroxychloroquine retinopathy is a cause of severe and progressive visual loss. Regular ophthalmological follow-up is mandotary to avoid hyroxychloroquine toxicity.
Hydroxychloroquine retinal toxicity
Keywords: Göz Hastalıkları